The polar ship Frithjof - Kjær, Kjell-G. (Polar Record, 2006)
Frithjof participated in several North Pole expeditions between 1898 and 1907 and was also involved in several relief expeditions. Her most frequent commander was Captain Johan Kjeldsen, who was an internationally famous ice pilot. Frithjof was built in 1884 at Stokke on Oslo fjord, Norway. After being employed in the sealing trade for some years, Frithjof was sold to an Icelandic concern. In 1891 she returned to Norwegian ownership and, in 1898, was chartered for Walter Wellman's North Pole expedition of the years 1898–1899. In 1900, she was the expedition ship for the Kolthoff expedition to Greenland, Spitsbergen and Jan Mayen. Between 1901 and 1904 she was engaged in Ziegler's North Pole expeditions both as expedition ship and as relief vessel. In 1903 the Swedish government chartered Frithjof in order to search for the Nordenskjöld expedition in the Antarctic. In 1906–7 the ship was again chartered for Wellman's North Pole airship expeditions. In late September 1907, Frithjof sailed from Tromsø on a relief expedition to search for Laura , an expedition vessel to Greenland that had not been heard of for three months. On 5 October 1907 she was lost in a storm off Iceland and only one man survived from her crew of 17.